Composition of the sinking particle flux in a hot spot of dinitrogen fixation revealed through polyacrylamide gel traps - Ababou, Fatima-Ezzahra; Le Moigne, Frédéric A. C.; Cornet-Barthaux, Véronique; Taillandier, Vincent; Bonnet, Sophie (Frontiers in Marine Science, 2024)
Diazotrophs regulate marine productivity in the oligotrophic ocean by alleviating nitrogen limitation, contributing to particulate organic carbon (POC) export to the deep ocean. Yet, the characterization of particles composing the sinking POC flux has never been explored in such ecosystems. Moreover, the contribution of the direct gravitational export of diazotrophs to the overall flux is seldom assessed. Here we explore the composition of the sinking POC flux in a hot spot of N2 fixation (the western sub-tropical South Pacific) using polyacrylamide gel-filled traps deployed at two stations (S05M and S10M) and three depths (170 m, 270 m, 1000 m) during the TONGA expedition (November-December 2019). Image analyses of particles collected in the gels was used to classify them into 5 categories (fecal aggregates, phytodetrital aggregates, mixed aggregates, cylindrical fecal pellets, and zooplankton carcasses). Fecal aggregates were the most abundant at both stations and all depths and dominated the flux (average of 56 ± 28% of the POC flux), followed by zooplankton carcasses (24 ± 19%), cylindrical fecal pellets (15 ± 14%) and mixed aggregates (5 ± 4%), whereas phytodetrital aggregates contributed less (<1%). Since N isotope budgets show that export is mainly supported by diazotrophy at these stations, these results suggest that the diazotroph-derived N has been efficiently transferred to the foodweb up to zooplankton and fecal pellets before being exported, pleading for an indirect export of diazotrophy. However, random confocal microscopy examination performed on sinking particles revealed that diazotrophs were present in several categories of exported particles, suggesting that diazotrophs are also directly exported, with a potential contribution to overall POC fluxes increasing with depth. Our results provide the first characterization of particle categories composing the sinking flux and their contribution to the overall flux in a hot spot of N2 fixation.